INDIA TO CANADA: A STUDY ON THE INFLUENCE OF SOCIO-ECONOMIC FACTORS ON THE EMOTIONAL WELL-BEING OF INDIAN IMMIGRANT MOTHERS - Pandian, Lydia (My University, 2025)
I critically examine the intersection of immigration, socio-economic stability, gendered labour roles, systemic racism, patriarchy, and colonial legacies, highlighting how systemic barriers, cultural expectations, and social support structures shape the lived experiences of Indian immigrant mothers in Canada. I adopted a Global South Indigenous arts-based methodology - 'Kolam' amplifying Indian immigrant mothers' voices in the Greater Toronto Area (GTA), exploring their struggles, determination, and conceptualizations of emotional well-being in the face of economic precarity and socio-cultural transition. I begin by tracing the historical trajectory of Indian women's socio-political status, from ancient matriarchal traditions to the rise of patriarchal structures and the impact of colonial rule. I examine how patriarchy and colonial ideologies marginalize Indian women by restructuring labour, education, and mobility, confining them to roles of dependence and caregiving. These historical patterns continue to shape their experiences even after transnational migration, reinforcing gendered hierarchies within both Indian diasporic kinship and Canadian institutions. I used a Global South Indigenous arts-based participatory approach and in-depth interviews grounded in Critical Race Feminism to capture the complexities of Indian immigrant mothers' pre- and post-migration experiences. Twenty Indian immigrant mothers from diverse socio-economic backgrounds in the GTA participated by creating visual art and verbal narratives about their experiences with support. I have used a narrative analysis approach to examine interview transcripts and to co-construct visual analysis of the artwork produced by the participants. The findings reveal key challenges such as employment insecurity, racialized gender norms, financial dependency, systemic racism, social isolation, and the lack of culturally sensitive mental health services. The study also interrogates the enduring impact of colonial histories on immigration policies, racialized labour markets, and the exclusion of immigrant women from social and economic mobility. By situating Indian immigrant mothers' experiences within the intersecting frameworks of patriarchy, colonialism, and immigration, this dissertation challenges dominant immigration narratives that often overlook the gendered and racialized struggles of Indian Immigrant Mothers in specificity. This research contributes to social work scholarship and immigrant mental health research by offering a critical analysis of the socio-economic determinants affecting Indian immigrant mothers. By centering their voices, this study advocates for a transformative, intersectional approach to immigrant mothers' well-being, ensuring that policy reforms and mental health services respond to the unique realities of racialized, gendered migration.
SOCIO-ECONOMIC IMPACT ON INDIAN IMMIGRANT MOTHERS' WELL-BEING
Keywords: Immigrant Mothers, Well being, Global South Indigemous methedology, Arts based community research, Socio- Economic precocity